2012
DOI: 10.1111/j.1743-6109.2012.02711.x
|View full text |Cite
|
Sign up to set email alerts
|

The Somatic and Autonomic Innervation of the Clitoris; Preliminary Evidence of Sexual Dysfunction After Minimally Invasive Slings

Abstract: Introduction Vaginal sling procedures may have a negative effect on sexual function due to damage to vascular and/or neural genital structures. Even though autonomic innervation of the clitoris plays an important role in female sexual function, most studies on the neuroanatomy of the clitoris focus on the sensory function of the dorsal nerve of the clitoris (DNC). The autonomic and somatic pathways in relationship to sling surgery have up to the present not been described in detail. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…In a systematic review evaluating 21 articles assess- ing sexual functions and/or coital incontinence following continence surgery in the absence of prolapse in 1,271 women, there was significant reduction in coital incontinence postoperatively [2]. Similar results were observed in other studies [4,8,18,30]. Although some studies have shown significant improvement in sexual functions after the decrease or disappearance of coital incontinence in the postoperative period, other studies have not supported this finding [2,31].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In a systematic review evaluating 21 articles assess- ing sexual functions and/or coital incontinence following continence surgery in the absence of prolapse in 1,271 women, there was significant reduction in coital incontinence postoperatively [2]. Similar results were observed in other studies [4,8,18,30]. Although some studies have shown significant improvement in sexual functions after the decrease or disappearance of coital incontinence in the postoperative period, other studies have not supported this finding [2,31].…”
Section: Discussionsupporting
confidence: 63%
“…The mean age of menopause was 46.7 ± 5.2 (31-53); the mean number of years since menopause was 7.5 ± 5.6 (0. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The mean number of deliveries were 2.9 ± 1.4 (0-9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After TVT, the vascularization of clitoral erectile tissues might be altered, as shown by colour Doppler ultrasonography. 99 By contrast, TOT procedures are not associated with orgasmic dysfunction, as confirmed by Bekker et al 100 They showed that the dorsal nerve of the clitoris was not disturbed during placement of a TVT-O, whereas autonomic innervation of the vaginal wall and clitoris was disrupted by the TVT procedure. Elzevier et al 101 reported deterioration in clitoral sensitivity and tumescence after TOT and TVT-O in 11.5% and 10% of cases, respectively.…”
Section: In 2012mentioning
confidence: 76%
“…We believe that a subgroup of women who derive their primary orgasmic function from vaginally elicited orgasms, that is, through penetration or stimulation of the anterior vaginal wall and periurethral female prostate region, could lose this response postoperatively after placement of the midurethral sling. The dissection for, and placement of, the midurethral sling clearly is likely to compromise the neural integrity of the anterior vaginal wall and periurethral female prostatic tissue 4, 5, 10, 13, 39…”
Section: Discussionmentioning
confidence: 99%